Pemetaan Kerusakan Jaringan Jalan Poros Samarinda - Melak Kabupaten Kutai Barat - Ferry Nicky Adrian Sardan; Dawamul Arifin; Shabri Indra Suryalfihra; Romansah Wumu; Andi Baso Sofyan A. P. (Journal of Geomatics Engineering, Technology, and Science, 2024)
The background of this research is due to the efforts to repair roads in Kutai Barat Regency, which are unevenly distributed. As a result, there are still many damaged road sections, including the Samarinda - Melak main road, thus necessitating a road condition assessment. The purpose of this research is to map the damage level of the Samarinda - Melak axis road. This research requires understanding in the field of geomatics to carry out measurement and mapping activities. The method used in the measurement activities is the tachimetry method which is then processed using Autocad Civil 3D, while checking road conditions is carried out directly at the measurement location. The results obtained in this study are a map of road damage, cross-sectional maps, and the level of road damage. The results show that the classification of damage on the Samarinda - Melak main road includes potholes, stripping, and distortion. Along the Samarinda - Melak main road, it can be observed that 57% of road damage is classified as potholes, 23% as distortion, and 20% as stripping.